A Comprehensive Network Integrating Signature Microbes and Crucial Soil Properties During Early Biological Soil Crust Formation on Tropical Reef Islands - Wang, Lin; Li, Jie; Zhang, Si (Frontiers in Microbiology, 2022)
Biological soil crusts (BSCs/biocrusts), which are distributed across various climatic zones and well-studied in terrestrial drylands, harbor polyextremotolerant microbial topsoil communities and provide ecological service for local and global ecosystem. Here, we evaluated BSCs in the tropical reef islands of the South China Sea. Specifically, we collected 41 BSCs, subsurface, and bare soil samples from the Xisha and Nansha Archipelagos. High-throughput amplicon sequencing was performed to analyze the bacterial, fungal, and archaeal compositions of these samples. Physicochemical measurement and enzyme activity assays were conducted to characterize the soil properties. Advanced computational analysis revealed 47 biocrust-specific microbes and 10 biocrust-specific soil properties, as well as their correlations in BSCs microbial community. We highlighted the previously underestimated impact of manganese on fungal community regulation and BSCs formation. We provide comprehensive insight into BSCs formation networks on tropical reef islands and established a foundation for BSCs-directed environmental restoration.